A Comparative Study Microbial for Biomass formed in calcareous soil cultivated corn with that cultivated by soy bean - Osama HusamFadhil Al- Azzawy; Ghaith Mohammad Kassim (Mesopotamia Journal of Agriculture)
A set of experiments were conducted in the Department of soil & water sciences resources of the college of Agaric. Forestry, University of Mosul  to study the effect of root exudates secreted by the tap roots of legume crop (represented by soybean) and fiber roots (represented by corn and barley) grown under different levels of salinity (2.5, 1,5 dS m-1 ) on soil microbial biomass ( MB-C ) at two periods of growth (40 and 80 days ) using a complete Randomized Design with three replicates for each treatment. There Uncultivated pots for each level of salinity were also included for comparison, and included a comparison between the microbial biomass of the rhizosphere soil with that of the non- rhizosphere. The MB-C of 10 different treatments were chosen from the tow experiments in order to measure the MB-C with two  different methods  ( FIM , SIRM ) in to obtaine a simple equations which explain the mathematical relationships between these two methods.Results indicated that :  Root exudates of  corn plant was generally less than that of soy bean. also decreased with age specially under soy bean. The MB-C under soy bean crop was nearly double of that measured under corn crop in both rhizosphere and non- rhizosphere soils. A negative relationship was oblained between the increases in the level of salinity and the MB-C .